Printable perovskite diodes for broad-spectrum multienergy X-Ray detection - Shabbir, Babar (2023)
Multienergy X-ray detection is critical to effectively differentiate materials in a variety of diagnostic radiology and nondestructive testing applications. Silicon and selenium X-ray detectors are the most common for multienergy detection; however, these present poor energy discrimination across the broad X-ray spectrum and exhibit limited spatial resolution due to the high thicknesses required for radiation attenuation. Here, an X-ray detector based on solution-processed thin-film metal halide perovskite that overcomes these challenges is introduced. By harnessing an optimized n-i-p diode configuration, operation is achieved across a broad range of soft and hard X-ray energies stemming from 0.1 to 10's of keV. Through detailed experimental and simulation work, it is shown that optimized Cs0.1 FA0.9 PbI3 perovskites effectively attenuate soft and hard X-rays, while also possessing excellent electrical properties to result in X-ray detectors with high sensitivity factors that exceed 5 × 103 µC GyVac-1 cm-2$μ {\rm{C}}\;{{\bf Gy}}_{{\rm{Vac}}}^{ - 1}\;{\rm{c}}{{\rm{m}}^{ - 2}}$ and 6 × 104 µC Gy-1 cm-2 within soft and hard X-ray regimes, respectively. Harnessing the solution-processable nature of the perovskites, roll-to-roll printable X-ray detectors on flexible substrates are also demonstrated.